2015
DOI: 10.1002/ijc.29398
|View full text |Cite
|
Sign up to set email alerts
|

Activation of aryl hydrocarbon receptor promotes invasion of clear cell renal cell carcinoma and is associated with poor prognosis and cigarette smoke

Abstract: Although exposure to environmental pollutants is one of the risk factors for renal cell carcinoma (RCC), its relationship with carcinogenesis and the progression of RCC remains unknown. The present study was designed to elucidate the role of the aryl hydrocarbon receptor (AhR), a major mediator of carcinogenesis caused by environmental pollutants, in the progression of RCC. The expression of AhR was investigated in 120 patients with RCC using immunohistochemistry, and its relationship with clinicopathological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 44 publications
0
33
0
Order By: Relevance
“…It was also reported that AhR mRNA overexpression in oral squamous cell carcinomas was due to elevated levels of nuclear AhR, whereas in adjacent normal tissue, the receptor was primarily cytosolic [35]. A similar distribution of the receptor protein was also observed in kidney tumors (nuclear) vs. normal renal tissue (cytosolic) and the AhR was a negative prognostic factor but was only expressed in 14/102 of the kidney tumors examined [36]. It is possible that increased nuclear localized of the receptor in some tumors may have some functional significance, thus the future application of selective AhR modulators (SAhRMs) that target specific tumors will require a personalized medicine approach and require prior knowledge of endogenous AhR expression in the tumor of interest and its intracellular location (nuclear vs cytosolic).…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 70%
“…It was also reported that AhR mRNA overexpression in oral squamous cell carcinomas was due to elevated levels of nuclear AhR, whereas in adjacent normal tissue, the receptor was primarily cytosolic [35]. A similar distribution of the receptor protein was also observed in kidney tumors (nuclear) vs. normal renal tissue (cytosolic) and the AhR was a negative prognostic factor but was only expressed in 14/102 of the kidney tumors examined [36]. It is possible that increased nuclear localized of the receptor in some tumors may have some functional significance, thus the future application of selective AhR modulators (SAhRMs) that target specific tumors will require a personalized medicine approach and require prior knowledge of endogenous AhR expression in the tumor of interest and its intracellular location (nuclear vs cytosolic).…”
Section: Role Of the Ahr In Carcinogenesismentioning
confidence: 70%
“…In TRAMP mice which are AR-positive, the evidence suggests that the AhR and its ligands are tumor growth inhibitory, although some mixed results were observed for TCDD (Fritz et al 2007; Fritz et al 2009; Moore et al 2016). Results of limited studies in urinary tract tumors suggest that the AhR and its ligands increase invasion (Ishida et al 2010), whereas in kidney cancer cell lines the results are contradictory and may be cell context-dependent (Callero et al 2012; Ishida et al 2015). …”
Section: The Ahr and Its Ligand In Tumorigenesis And Cancer Chemotherapymentioning
confidence: 99%
“…However, in other tumors, an inverse correlation is found, which suggests that the role of AHR during progression of different tumors is complicated (Portal-Nuñez et al 2012). Generally, cytoplasmic AHR and nuclear AHR are predominantly observed in non-neoplastic tissues and in malignant tissues, respectively (Ishida et al 2015). Ligand binding alters AHR conformation to expose its nuclear localization sequence (NLS), which results in nuclear import.…”
Section: Discussionmentioning
confidence: 99%
“…After 24-h incubation at 37 °C, cells were fixed with 3.7 % formaldehyde and stained in 0.1 % crystal violet for 15 min, and non-migratory cells were removed by scraping the upper surface of the chamber membrane. The invasive cells were counted under a light microscope (Ishida et al 2015). …”
Section: Methodsmentioning
confidence: 99%